1985
DOI: 10.1002/art.1780280417
|View full text |Cite
|
Sign up to set email alerts
|

Raynaud's phenomenon of a single digit following local intradermal bleomycin sulfate injection

Abstract: Bleomycin sulfate, administered parenterally alone and in combination with vinblastine sulfate for treatment of various neoplastic diseases, has been associated with the development of Raynaud's phenomenon (1-5). Additionally. bleomycin therapy has been associated with a number of varied skin reactions, including hyperpigmentation, sclerosis, gangrene, indurated plaques, and hyperpigmented nodules (6).Several recent reports have described the use of intralesional injections of bleomycin sulfate for treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
1
7
0
2
Order By: Relevance
“…Hypopigmentation, 20,37 pneumonialike symptoms, 38 and both atrophic and hypertrophic scarring 24,31,37 are rare occurrences. Although sporadically seen with intralesional bleomycin, documentation of Raynaud's phenomenon, 34,35,[39][40][41][42][43][44][45][46] anaphylaxis, 17,25,28,41 and flagellate hyperpigmentation 41 does exist in the literature. These events occur more commonly with intravenous administration of the drug.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Hypopigmentation, 20,37 pneumonialike symptoms, 38 and both atrophic and hypertrophic scarring 24,31,37 are rare occurrences. Although sporadically seen with intralesional bleomycin, documentation of Raynaud's phenomenon, 34,35,[39][40][41][42][43][44][45][46] anaphylaxis, 17,25,28,41 and flagellate hyperpigmentation 41 does exist in the literature. These events occur more commonly with intravenous administration of the drug.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Other toxic side effects of BLM are reversible but Raynaud's phenomenon persists after cessation of the drug [10]. In the ease presented here, the lesion was found to persist in the same finger 3 years after the injection.…”
Section: Raynaud's Phenomenon Following Intralesional Bleomycin Injecmentioning
confidence: 47%
“…To the Editor: Bleomycin (BLM) is recommended as an alternative therapy for cutaneous tumors [l]. Although many complications have been reported to be associated with parenteral administration of BLM [2][3][4][5][6], reports about the complications of intralesional therapy are sparse [7][8][9][10]. We describe a patient who developed Raynaud's phenomenon limited to the intralesional BLM injected digit.…”
Section: Raynaud's Phenomenon Following Intralesional Bleomycin Injecmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well demonstrated that BLM has a direct action on endothelial cells by production of oxidant agents (Adamson and Bowden, 1974;Lazo and Humphreys, 1983). Raynaud's phenomenon has sometimes been observed following BLM iv administration and is believed to be a clinical manifestation of BLM toxicity to the endothelium (Vogelzang et al, 1981;Cohen et al, 1973;Smith et al, 1985). The location of the skin lesions close to the IA delivery site of the drug suggests that the concentration of BLM at this level may be toxic to the skin capillaries.…”
Section: Discussionmentioning
confidence: 99%